1990
DOI: 10.1164/ajrccm/141.5_pt_1.1289
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Pulmonary Eosinophilia in Mice byAscaris suumExtract

Abstract: The transnasal administration of an extract of the parasite Ascaris suum (Asc) to C57BL/6 mice for 3 wk produced marked eosinophilia in the bronchoalveolar lavage (BAL) fluid. This pulmonary eosinophilia was not accompanied by blood eosinophilia. The oral administration of cyclosporin, 50 mg/kg body weight, every other day significantly suppressed the pulmonary eosinophilia. Athymic C57BL/6-nu/nu mice failed to develop pulmonary eosinophilia. These data indicate that pulmonary eosinophilia caused by this paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 8 publications
3
32
0
Order By: Relevance
“…CsA, paradoxically, increased the A. fumigatus-induced lung disease. This latter fmding contrasts with the results of Nogami et ai, who found that CsA efficiently blocked Ascaris antigen-induced pulmonary eosinophilia [35]. However, other reports showed that CsA caused an augmentation of DTH in rats or guinea pigs [36].…”
Section: Discussionmentioning
confidence: 58%
“…CsA, paradoxically, increased the A. fumigatus-induced lung disease. This latter fmding contrasts with the results of Nogami et ai, who found that CsA efficiently blocked Ascaris antigen-induced pulmonary eosinophilia [35]. However, other reports showed that CsA caused an augmentation of DTH in rats or guinea pigs [36].…”
Section: Discussionmentioning
confidence: 58%
“…Using these mice, a series of studies showed that MCs play an important role in the airway response (30,(33)(34)(35)(36). Although some studies showed that MC deficiency resulted in attenuated eosinophil-mediated airway inflammation (34,37), other studies indicated a lack of MC participation in AHR (38)(39)(40). These conflicting roles for MCs may be due to experimental variables, such as the inclusion or omission of artificial adjuvants, or the use of relatively low doses of Ag for sensitization (30,33,34,36).…”
Section: Discussionmentioning
confidence: 99%
“…When studying mechanisms of allergic airway disease in animal models, mast cell-deficient mice have variable decreases in eosinophil numbers (31,32) following allergen challenge, but systemically sensitized and challenged mast cell-deficient mice are capable of developing a Th2 response, airway inflammation, and AHR similar to WT control mice (33)(34)(35)(36). In most of these studies, allergen sensitization was achieved by systemically injecting the allergen in combination with an adjuvant, while other studies, using less potent sensitization protocols, demonstrated a more obvious role for mast cells in the development of AHR (37,38).…”
Section: Discussionmentioning
confidence: 99%